Nonspecificity of 35 kDa protein: A proposed marker for the differential diagnosis of M. avium infection in the Indian population - Gupta Kapil; Mahajan Rajiv; Khuller Gopal; Verma Indu (Wolters Kluwer Medknow Publications, 2010)
Objective: The subunit vaccine strategies and development of various diagnostic reagents for Mycobacterium avium infection relies on the presence of secreted, species-specific mycobacterial antigens. The M. avium 35 kDa protein has been suggested as a candidate for vaccine/diagnostic reagent, specifically for M. avium infection. The present study was conducted to evaluate the diagnostic specificity of the M. avium 35 kDa protein in the Indian population. Materials and Methods: Culture filtrate proteins were isolated by growing the bacilli in modified Youman′s medium. The 35 kDa protein was purified by high-resolution preparative sodium dodecyl sulfate-polyacrylamide gel electrophoresis and a blast search was carried out. Western blotting was performed with either monoclonal antibody CS-38 or serum samples of tuberculosis (TB) patients. The 35 kDa-specific immunoglobulin G antibody titer was estimated in the sera of TB patients and healthy individuals by indirect enzyme-linked immunosorbent assay (ELISA). Results: Despite the absence of gene for the 35 kDa protein, the sera of TB patients and TB patient′s contacts nonspecifically recognize it. Of 109 TB patients tested, the sera of 84 patients in ELISA (percentage recognition = 87.5%) and 27 of 29 TB patients tested in western immunoblotting (percentage recognition = 93.10%) recognized the M. avium 35 kDa protein, while with sera of TB patient′s contacts, the recognition was 50%. Conclusion: Contrary to Western studies, the M. avium 35 kDa protein does not seem to be a good candidate for the specific diagnosis of M. avium infection in the Indian population.